Can weekly frequency of plyometric training impair strength and power? A short-term comparison in regional-level jump athletes - Li, Ang; Zhang, Hongbo; Peng, Changwei; Wu, Yutong; He, Jia (Frontiers in Physiology, 2025)
ObjectiveTo compare the short-term effects of two versus three weekly PT sessions on strength and jump performance in competitive jumpers, and to examine associations between delayed onset muscle soreness (DOMS) and week-to-week performance changes.MethodsThirty-nine male regional-level high and long jump athletes (17–23 years) completed a 4-week non-randomized observational cohort study. In Week 1 all performed two PT sessions; from Week 2, athletes continued with either two sessions per week (n = 19) or increased to three (n = 20). In Week 4, both groups reduced to two weekly sessions as part of a taper, such that Week-4 outcomes reflect shared recovery rather than continued frequency differences. Assessments at baseline and Weeks 1–4 included isometric mid-thigh pull (IMTP), countermovement jump (CMJ), squat jump (SJ), and standing long jump (SLJ). DOMS was recorded weekly. Mixed-design ANOVAs tested group × time effects, and participant-level correlations examined DOMS associations with performance changes.ResultsSignificant main effects of time were found for IMTP, SLJ, CMJ, and SJ (all p < 0.001). The 2×/week group showed steady improvements in IMTP and SLJ, while the 3×/week group experienced early decrements during intensified loading, followed by recovery in Week 4 during the taper phase. Participant-level analyses revealed significant negative correlations between DOMS and ΔIMTP (r = −0.38, 95% CI [–0.53, −0.21]) and ΔSLJ (r = −0.63, 95% CI [–0.73, −0.50]); weaker associations were observed for ΔCMJ (r = −0.21, 95% CI [–0.37, −0.03]) but not for ΔSJ.ConclusionTraining twice weekly promoted more consistent gains, while three weekly sessions induced transient impairments linked to higher DOMS. Week-4 convergence reflected taper-related recovery rather than sustained frequency effects. Monitoring soreness may help coaches optimize load and recovery in jump athletes.